Efektifitas Metode Konseling Individu Dalam Mengendalikan Tingkat Kenakalan Remaja Di SMAN 1 Kauman Tahun Pelajaran 2017/2018 - Wiratama, Reza (RONTAL: Jurnal Keilmuan Pancasila dan Kewarganegaraan, 2018)
The purpose of this research is to know how effectiveness individual counseling services by counselor teachers in overcoming difficulties learning to study students SHS 1 Kauman Tulungagung regency. The type of this research is qualitative descriptive research. Research subject are the students who perform the act of mischief in mischief in SHS I Kauman. While the object of this study is an individual counseling service implemented by the tutor teacher to overcome the level of juvenile delinquency. To collect data in this research the researcher use observation and interview technique analyzed with qualitative and narrative concluded. From the results of this study the authors found that the level of Effectiveness of Individual Counseling Services in Controlling the Delinquency Level of Youth in SMA Negeri 1 Kauman Tulungagung District is very effective to handle the problem of juvenile delinquency of students of SMA Negeri 1 Kauman, proved that after the students actors mischief adolescents in SHS 1 Kauman have the will to change their actions that violate the rules that have been determined by the school.